OPTIMALISASI SEKTOR UNGGULAN UNTUK MENINGKATKAN KINERJA EKONOMI DAN SERAPAN TENAGA KERJA DI PROVINSI LAMPUNG - Gunawan, Muhammad Chandra; Alamin, Farozak; Mariska, Mega; Purwaningsih, Vitriyani Tri; Malia, Rizka (Politeknik Bisnis Indonesia, 2024)
The following research aims to analyze the leading sectors and their differences in absorbing labor in Lampung Province. The research objects include 5 districts/cities in Lampung, namely Bandar Lampung, South Lampung, East Lampung, Central Lampung and North Lampung. This research is motivated by the still high rates of unemployment and poverty caused by an imbalance between the lack of employment opportunities and economic and development inequality. Therefore, it is important to identify leading sectors as priorities in economic development and employment. To find out the leading sectors, we used the LQ method, normality test to see the distribution of data, and difference tests (paired sample t-test and Wilcoxon test) using Eviews12 to examine the differences in employment absorption between the leading and non-leading sectors. The results of this research show that there are several sectors that are superior in each district/city based on the LQ analysis carried out. The results of different tests show that leading sectors can absorb significantly more labor than non-leading sectors. Efforts to develop and optimize leading sectors can be an effective strategy for reducing unemployment and improving community welfare in Lampung Province. Keywords: Labor, leading sectors, unemployment, economic improvement.